Modern materials for cast rolls of hot strip mills - Vyacheslav Goryany; Olga Myronova (Zaštita Materijala)
The requirements for the work rolls for the various roll stands of hot strip mills are shown. The modern materials for cast rolls are analyzed and the operational performance of different types of rolls in different stands of the rolling mill is described. The trends in improvement of rolls performance were presented.